On the CP exterior product of Lie algebras - Zeinab Araghi Rostami (AUT Journal of Mathematics and Computing, 2023)
In this paper, under certain conditions, we show that the non-abelian CP exterior product distributes over direct product of Lie algebras. Then we present some properties about CP extension of Lie algebras.